Synthesis and Characterization of Metal Chelates of Ti(III), Cr(III), Rh(III), V(IV), Zr(IV) and Pt(IV) with 2-Mercapto-3-butyl-quinazoline-4-one - Pandey, R.N.; Kr. Singh, Rajnish; Ranjan, Manoj; Priya (Asian Journal of Chemistry, 2010)
2-Mercapto-3-butyl-quinazoline-4-one forms trans-octahedral chelates having general formula [ML2A2]X (M = Ti, Cr, Rh; A = Py/H2O; X = Cl/NO3) and [M(LH)4A2]X4 (M = Pt, Zr; A = Py/ H2O; X = NO3/Cl). Tentative structure of all the complexes have been assigned using micro-elemental analyses, magnetic moment, conductometric, IR, UV-vis and 1H NMR spectra data.